Metformin: Activation of 5′ AMP-activated protein kinase and its emerging potential beyond anti-hyperglycemic action - Goel, Sanjay; Singh, Ravinder; Singh, Varinder; Singh, Harmanjit; Kumari, Pratima; Chopra, Hitesh; Sharma, Rohit; Nepovimova, Eugenie; Valis, Martin; Kuca, Kamil; Emran, Talha Bin (Frontiers in Genetics, 2022)
Metformin is a plant-based drug belonging to the class of biguanides, known to treat type-2 diabetes mellitus (T2DM). The drug and controlling the blood glucose levels have improved the body’s response to insulin. Besides this, trials have identified the cardio-protective potential of metformin in the diabetic population receiving the drug. Activation of 5' AMP-activated protein kinase (AMPK) remains the major pathway for these potential beneficial effects of metformin. Over the years, much emphasis has been given to the potential indications of metformin beyond its anti-diabetic use. This review aims to study and appraise various other potential uses of metformin mainly mediated by the activation of AMPK. We also discussed various mechanisms (other than AMPK activation) via which metformin could produce beneficial effects in these conditions. Databases like PubMed /MEDLINE and Embase were searched for literature relevant to the review's objective. Reports from both research and review articles were considered. Metformin has diversified effects on the human body systems. It has been shown to exert anti-inflammatory, antioxidant, cardio-protective, metabolic, neuroprotective, anti-cancer and antimicrobial effects and has now even been spotted to be of effective against SARS-CoV-2. Among all, AMPK pathway was recognized to be the responsible one for its efficiency and effectiveness. Owing to its magnanimous potential, it does hold the capability of becoming a part of treatment regimens for diseases apart from T2DM.